MENUMBUHKAN PENGETAHUAN MASYARAKAT TENTANG DAGUSIBU OBAT ANTIBIOTIK DAN TETES MATA DI DAERAH LIMBANGAN SUMBERAHAYU - Anwar, Khoirul; Darmanto; Septiani, Reni; Putri, Netty Fitriana; Qiftiyah, Maemunatussa’dayatul; Syahla; Zaneta, Aulia; Renitasari, Delta Ayu; Utami, Fuji; Setyadi, Achmad Umar (LPPM Universitas Widya Dharma Klaten, 2025)
Knowledge about medicine must be possessed by all levels of society. The widespread distribution of counterfeit medicines and errors in using DAGUSIBU medicines have become one of the efforts to increase public knowledge in using and managing medicines. This community service aims to provide DAGUSIBU education to the community, especially women from the Women's Farmers Group (KWT) in Krajan Village, to increase community knowledge about the correct (rational) use of medicines and procedures for storing and disposing of medicines that have been damaged or expired correctly. The method used in this service is to increase knowledge about the Use of Storing and Disposing of Medicines (DAGUSIBU). With this outreach, it is hoped that knowledge of drug use will be increased. Participants in this extension were given material about DAGUSIBU directly and supported with props in the form of medicine as an example of the application of DAGUSIBU in active discussions. The output of this service shows an increase in the knowledge of counseling participants about drugs through DAGUSIBU. Therefore, this outreach needs to be continued to monitor and improve cadres as good information agents to the general public, especially in Krajan Village.